2018
DOI: 10.1007/s40261-018-0690-9
|View full text |Cite
|
Sign up to set email alerts
|

Cost Estimate of Immune-Related Adverse Reactions Associated with Innovative Treatments of Metastatic Melanoma

Abstract: This study may represent a useful tool to understand the economic burden associated with the management of irAEs associated with patients affected by metastatic melanoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 27 publications
0
4
1
Order By: Relevance
“…In the current study, patients treated with ICIs who did not develop irAEs had significantly lower costs and HRU than those developing irAEs that required treatment. Studies previously published examining the costs related to the management of irAEs have been conducted in France [30] and Italy [31], and thus are not comparable to the current study conducted in the U.S. owing to differing health care systems. Compared with chemotherapy, a U.S. real-world study found that ICI monotherapy resulted in fewer AE-related visits among patients with metastatic NSCLC receiving first-line treatment [5].…”
Section: Discussioncontrasting
confidence: 68%
“…In the current study, patients treated with ICIs who did not develop irAEs had significantly lower costs and HRU than those developing irAEs that required treatment. Studies previously published examining the costs related to the management of irAEs have been conducted in France [30] and Italy [31], and thus are not comparable to the current study conducted in the U.S. owing to differing health care systems. Compared with chemotherapy, a U.S. real-world study found that ICI monotherapy resulted in fewer AE-related visits among patients with metastatic NSCLC receiving first-line treatment [5].…”
Section: Discussioncontrasting
confidence: 68%
“…Balaji et al reported that around 20% of patients treated with immunotherapy require inpatient hospitalization, with most of these attributed to irAEs. The hospitalization rates for patients receiving dual-agent immunotherapy treatment were notably higher, estimated to have more than a six-fold increase in the odds of hospital admission compared to those treated with single-agent immunotherapy [17,18]. As reported by a single institute study from Massachusetts General Hospital in the United States, the annual cumulative cost of admissions related to irAEs easily reaches into the millions, exceeding USD 3000 per day of admission [19].…”
Section: Discussionmentioning
confidence: 96%
“…Such predictor could greatly impact clinical practice as it could prompt the early start of add-on therapies, thus possibly preventing the accrual of organ damage. In fact, irAEs are associated with remarkable morbidity and mortality, as well as significant costs [7] that could be reduced with a timely start of second-line therapies.…”
Section: Discussionmentioning
confidence: 99%